Learning Model Integration Teams Games Tournament (TGT) and Gaming Media Uno Stacko to Social Studies Learning Outcomes In the classroom V Elementary School 2 Bahonsuai - Mariam, Ine; Hasan, Hasan; Idrus, Idrus (Journal of Education Method and Learning Strategy, 2024)
Education is very important capital in development a country of use obtain source Power quality human being, because through arrangement good education​will produce good graduates too. Therefore​that’s an increase quality education also means improvement quality source Power man. As for the formula problem Does the integration of the Teams Games Torunemaent (TGT) model and the Uno Stacko game media have an effect on social studies learning outcomes for class V of SD Negeri 2 Bahonsuai, objectives study Based on formulation the problem above so objective study namely to find out the integration of the Teams Games Torunemaent (TGT) model and the Uno Stacko game media which influences the social studies learning outcomes for class V SD Negeri 2 Bahonsuai, method This research is a type of quantitative research with experimental methods, results study The research instrument test is used to determine the level of validity, reliability, level of difficulty and distinguishing power of the questions. Before examining the average similarity between the two classes using independent sample t-test analysis, a normality test, homogeneity test, and N-Gain test are needed first. After carrying out the normality test, homogeneity test, and N-Gain test in both classes, the data was sufficient to carry out hypothesis testing.